MEMBANGUN KARAKTER RELIGIUS MELALUI PEMBIASAAN NILAI-NILAI POSITIF DI LINGKUNGAN SEKOLAH DASAR - Paskaria Simbolon; Yakobus Ndona; Daulat Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to illustrate how students' religious character can be formed through positive behavioral habits in elementary schools. The approach used was qualitative with descriptive methods. Data collection techniques were conducted through observation, interviews, and document analysis. The research findings indicate that positive routines such as making prayer a habit before and after learning, instilling honesty, mutual respect, and concern for others, have a significant influence on building students' religious character. Schools play a crucial role as formal educational institutions in instilling religious values ​​through daily activities integrated into the teaching and learning process and social interactions among school members.